Penyelamatan Tungkai dengan Prosedur Darrach dan Teknik Tulang Tunggal pada Tumor Sel Raksasa pada Ulna (Campanacci Tipe 3): Laporan Kasus - Saputra, Rhyan Darma; Sadewa, Daffa; Dzikri, Dykall; Budiyanto, Sandya Naufal; Aji, Febriagi Bayu (Cermin Dunia Kedokteran, 2025)
Introduction: Giant cell tumor of bone (GCTB) is a rare, benign but locally aggressive tumor that uncommonly afects distal ulna. Case: This case is a 30-year-old female with worsening pain, swelling, and limited wrist motion. Imaging studies revealed cortical destruction and soft tissue infltration characteristic of an aggressive GCTB. Campanacci type 3 GCTB of the distal ulna was diagnosed and managed through limb salvage surgery using a combination of Darrach procedure and single bone technique.This combined approach aims to achieve tumor clearance while preserving limb function. Post-operative management included soft tissue closure using an abdominal fap. Conclusion: The case highlights the challenges in managing aggressive GCTBs of the distal ulna and demonstrates a viable limb salvage strategy. Long-term follow-up is recommended to evaluate functional outcomes and to monitor for recurrence, because tumor’s aggressive nature.